Design and Implementation of Four Bit Binary Shifter Circuit Using Reversible Logic Approach - Vandana Shukla; O. P. Singh; G. R. Mishra; R. K. Tiwari (Institute of Advanced Engineering and Science, 2015)
Shifter circuits are the key component of arithmetic logic unit as well as storage unit of any digital computing device. Designing these shifter circuits using reversible logic approach leads to create low power loss digital systems. Reversible circuit design approach is nowadays widely applicable in various disciplines such as Nanotechnology, Low power CMOS design, Optical computing etc. This paper presents two design approaches for four bit binary combinational shifter circuit with the help of different types of reversible logic gates. The proposed optimized design is simulated using Modelsim tool and synthesised for Xilinx Spartan 3E with Device XC3S500E with 200 MHz frequency.